Torsion of Wandering Spleen and its adherence to the right ovary - An unusual cause of recurrent pain abdomen - Gulati, Malvika (J Radiol Case Rep, 2020)
Wandering spleen is a rare condition in which the spleen is hypermobile due to laxity or lack of its supporting ligaments. It can be located anywhere in the abdomen besides its usual position. The other terms that are used to describe this condition are splenic ptosis, displaced spleen, dislocated spleen and ectopic spleen. Splenic torsion is a dreaded complication and the usual cause of symptoms. There is a high chance of missing the diagnosis as it remains asymptomatic or may be incidentally discovered on radio-imaging done for a different purpose. An acute abdomen is the most common presentation. Here we describe an unusual case presenting with torsion of the wandering spleen that was adherent to the right ovary.